Roots of Ergativity in Africa (and Beyond) - Antje Casaretto; Gerrit J. Dimmendaal; Birgit Hellwig; Uta Reinöhl; Gertrud Schneider-Blum (Studies in African Linguistics)
In the literature, it is often assumed that ergative constructions originate in passive constructions. The present contribution explores the likelihood of such a passive-to-ergative analysis for one language (Tima, Niger-Congo, Sudan), showing that this analysis cannot be substantiated and suggesting an origin in active constructions instead. This study is situated in its areal context (outlining similarities to split case marking systems across the region, especially in the Southern branch of Eastern Sudanic) and against the background of discussions in the Indo-Iranian family (from where the passive-to-ergative hypothesis presumably spread).